Acquired von Willebrand Syndrome and Platelet Function Defects during Extracorporeal Life Support (Mechanical Circulatory Support) - Schlagenhauf, Axel; Kalbhenn, Johannes; Geisen, Ulrich; Beyersdorf, Friedhelm; Zieger, Barbara (Hämostaseologie, 2020)
Patients with ventricular assist devices (VADs) and extracorporeal membrane oxygenation (ECMO) suffer from an increased risk for thromboembolic events as well as for hemorrhages. High shear stress in the mechanical device results in acquired von Willebrand syndrome (AVWS), characterized by a loss of high-molecular-weight multimers of von Willebrand factor (VWF) leading to an increased bleeding risk. Onset of AVWS occurs within hours, persists during the whole period of mechanical support, and subsides rapidly after explantation. Patients with the older HeartMate II exhibit more severe AVWS than those with the newer HeartMate III, thanks to lower shear stress in the latter. All ECMO and VAD patients exhibit thrombocytopathia and often thrombocytopenia which further increases the bleeding risk. Etiological models for AVWS are increased cleavage by the metalloproteinase ADAMSTS13, mechanical destruction of VWF, and shear-induced VWF binding to platelets. Platelet secretion defects may be caused by transient platelet activation leading to degranulation. AVWS can be diagnosed by detection of VWF multimers using gel-electrophoresis and functional assays of varying sensitivity (VWF ristocetin cofactor activity, VWF activity, VWF collagen binding). Platelet dysfunction is monitored using light transmission aggregometry and secretion defects are detectable using flow cytometry. Modest use of anticoagulants and a target-controlled therapy based on VWF parameters and other coagulation and platelet parameters are shown to be beneficial in this patient group. Persistent hemorrhages may be controlled with tranexamic acid and platelet concentrates. Prompt weaning from the device, when indicated, is the best therapeutic option to prevent recurrent bleeding.
Keywords: ventricular assist devices; ECMO; acquired von Willebrand syndrome; platelet secretion